Occurrence Download - GBIF.Org User (The Global Biodiversity Information Facility, 2017)
A dataset containing 3674 species occurrences available in GBIF matching the query: { "and" : [ "TaxonKey is Panicum repens L.", "HasCoordinate is true", "HasGeospatialIssue is false" ] } The dataset includes 3674 records from 127 constituent datasets; see https://api.gbif.org/v1/occurrence/download/0060922-160910150852091/datasets/export for details. Data from some individual datasets included in this download may be licensed under less restrictive terms.
Keywords: GBIF; biodiversity; species occurrences